2005
DOI: 10.1042/bj20050079
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the interaction between human milk oligosaccharides and the bacterial lectin PA-IIL of Pseudomonas aeruginosa

Abstract: One of the mechanisms contributing to the protection by breast-feeding of the newborn against enteric diseases is related to the ability of human milk oligosaccharides to prevent the attachment of pathogenic bacteria to the duodenual epithelium. Indeed, a variety of fucosylated oligosaccharides, specific to human milk, form part of the innate immune system. In the present study, we demonstrate the specific blocking of PA-IIL, a fucose-binding lectin of the human pathogen Pseudomonas aeruginosa, by milk oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 40 publications
8
109
2
4
Order By: Relevance
“…The groups of Imberty and Wimmerova endorsed our results by elucidating the 3-dimensional crystallographic and thermodynamic interactions of that lectin with the fucosylated lewis a (Le a ) receptor (which mediates P. aeruginosa binding to the lungs of cystic fibrosis patients) and with the competing milk saccharides (Mitchell et al, 2002;Perret et al, 2005).…”
Section: Introductionmentioning
confidence: 65%
“…The groups of Imberty and Wimmerova endorsed our results by elucidating the 3-dimensional crystallographic and thermodynamic interactions of that lectin with the fucosylated lewis a (Le a ) receptor (which mediates P. aeruginosa binding to the lungs of cystic fibrosis patients) and with the competing milk saccharides (Mitchell et al, 2002;Perret et al, 2005).…”
Section: Introductionmentioning
confidence: 65%
“…LecA is a D-galactose-binding lectin with high affinity for terminal glycans presenting an ␣-galactose residue at the nonreducing end (4,18). The LecB lectin has a high affinity for L-fucose and its derivatives (24,35). Several studies have suggested that blockade or inhibition of these lectins by specific carbohydrates may be useful for prevention and treatment of P. aeruginosa infections (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of L-fucose was evidenced by the absence of lectin binding to the control N-acetylated dendrimer library. A selection of hit sequences were resynthesized and their lectin binding characterized in detail by ELLA, 51 which identified hit FD2 as the most potent ligand with an IC 50 = 11 mM towards lectin UEA-I and a relative potency of 115 in reference to L-fucose, corresponding to a six-fold affinity enhancement per fucosyl group. Although the multivalency effect observed with FD2 was modest, it was confirmed by the observation of much weaker binding in the divalent and monovalent glycopeptide analogs of the dendrimer.…”
Section: Selection Of Fucose Lectin Inhibitors From Combinatorial Libmentioning
confidence: 99%